Nora Alter. The Essay Film After Fact and Fiction. Columbia UP, 2018. - Ervin Malakaj (Studies in 20th & 21st Century Literature, 2019)
Review of Nora Alter. The Essay Film After Fact and Fiction. Columbia UP, 2018. xii + 394 pp.
Keywords: film studies; essay film